Generation of Descriptors for the Text of a Technical Paper: A Case Study - Sridhar, Aparna; Sreelatha, G. (Journal of Information and Knowledge, 1993)
Many new and improved techniques for better and effective information retrieval are being developed by information scientists. Retrieval of information/documents, in response to a query, using document surrogates or descriptors generated automatically is one such approach. One of the methods in automatic indexing is single-term indexing which involves assigning of single-terms or descriptors for content representation. Index terms thus help in information retrieval and in analysing the document. In this experiment, an article in an established journal was chosen for the analysis. Using single-term automatic indexing methods, the title, the abstract and the text of the article were indexed and analysed to find out the expressiveness of the title and the abstract and whether the paper follows the APUPA pattern of information flow. The details of the experiment are discussed in the following article.